The Effect of Phase Angle on the Thermo-Mechanical Fatigue Life of a Titanium Metal Matrix Composite - Mark Whittaker (Materials, 2019)
The thermo-mechanical fatigue (TMF) behaviour of a Ti-6Al-4V matrix composite reinforced with SCS-6 silicon carbide fibres (140 μm longitudinal fibres, laid up hexagonally) has been investigated. In-phase and out-of-phase TMF cycles were utilized, cycling between 80–300 °C, with varying maximum stress. The microstructure and fracture surfaces were studied using electron backscatter diffraction (EBSD), energy-dispersive X-ray spectroscopy (EDS), scanning electron microscopy (SEM), profilometry, and optical microscopy. The results have shown the damaging effect of out-of-phase cycling with crack initiation occurring earlier than in in-phase tests and crack propagation rates being accelerated in out-of-phase cycles. Fatigue crack initiation has been shown to be sensitive to crystallographic texture in the cladding material and thermo-mechanical fatigue test results can be considered according to a previously proposed conceptual framework for the interpretation of metal matrix composite fatigue.